The Impact of Environmental and Behavioral Factors on the Incidence of Dengue Hemorrhagic Fever in Indonesia: Meta-analysis - Muhamad, Fadel T.; Azizah, R. (Poltekkes Kemenkes Palu, 2023)
Cases of dengue fever in Indonesia will increase to 143,000 by the end of 2022. The aim of the research is to examine the impact of environmental and behavioral factors on the incidence of dengue hemorrhagic fever in Indonesia. This research uses the Meta-Analysis Method with PICOS technology. Some sources of information used include Google Scholar, Research Gate, and Plos ONE, with the help of keywords such as